God has no favourites : the New Testament on first century religions - Scott, Basil (Minneapolis : Fortress Press, 2017)
The New Testament does not conform neatly to any modern attempts to define the Christian approach to other religions, argues Basil Scott. He confronts the questions: What does the New Testament tell us about religions? And what is its approach to those who were Gentiles, and to their beliefs and practices? He focuses his attention on the evidence presented by the New Testament itself, and especially on the attitude of its writers to the religions of their times.
Part I. Examining the data -- Religions in the Greek and Roman World -- Jewish religion -- Salvation through Christ and its implications for religions -- Relations between Christians and people of other religions -- Part II. The emerging picture -- God's view of people of other faiths -- God's treatment of religions -- God's way of salvation -- God's standards for Christian mission -- Concluding postscript.
Includes bibliographical references (page 202) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Christianity and other religions